Poder judiciário, serviço social e justiça restaurativa : um diálogo possível? - Oliveira, Fabiana Nascimento de (2015)
This study has as its theme the analysis of the impact of the use of restorative justice interventions of Social Work in Judiciary Brazilian. It is in an exploratory study of a qualitative nature and is based on the critical dialectical method. The investigation is to place the judiciary, specifically in the area of children and youth. Were used as study sources: documentary research in various documents relating to the profession and empirical research conducted through electronic questionnaires, where professionals of Social Services entered into this institutional context in the cities of Bethlehem / PA and Porto Alegre / RS recorded their contributions. The analysis procedures of the data were performed based on the theoretical reference Bardin, by Content Analysis. The results allow us to infer that the social workers know the proposal of Restorative Justice, but punctuate contradictions in use because, depending on how it is used, can either contribute to the guarantee of rights, as may also be levied and corroborate the reaffirmation of objetualizantes processes the subjects that are included in the working processes of the current justice system, hegemonic retributive, which captures even the work of social workers when inserting these work processes. It was found that the place of restorative justice in the professional exercise of social work is, however, conform in a nascent place, under construction, with the strong limiting its action hierarchical and conservative characteristics, still dominate the judiciary. It is said that this dialogue involving the judiciary, Social Services and Restorative Justice have been taking place over the ten years of implementation of Restorative Justice in Brazil and thus being built and strengthened, but still faces challenges of deepening in various fields of competence professional, including the production of knowledge of the area.